Learning and aging related changes in intrinsic neuronal excitability - Oh, M. M.; Oliveira, Fernando A.; Disterhoft, John F. (Frontiers in Aging Neuroscience, 2010)
A goal of many laboratories that study aging is to find a key cellular change(s) that can be manipulated and restored to a young-like state, and thus, reverse the age-related cognitive deficits. We have chosen to focus our efforts on the alteration of intrinsic excitability (as reflected by the postburst afterhyperpolarization, AHP) during the learning process in hippocampal pyramidal neurons. We have consistently found that the postburst AHP is significantly reduced in hippocampal pyramidal neurons from young adults that have successfully learned a hippocampus-dependent task. In the context of aging, the baseline intrinsic excitability of hippocampal neurons is decreased and therefore cognitive learning is impaired. In aging animals that are able to learn, neuron changes in excitability similar to those seen in young neurons during learning occur. Our challenge, then, is to understand how and why excitability changes occur in neurons from aging brains and cause age-associated learning impairments. After understanding the changes, we should be able to formulate strategies for reversing them, thus making old neurons function more as they did when they were young. Such a reversal should rescue the age-related cognitive deficits.